PTU-012 Faecal Calprotectin as Predictor of Small-Bowel Crohn's Disease in Capsule Endoscopy – A Systematic Review and Meta-Analysis. (17th August 2016) - Kopylov, U; Yung, DE; Engel, T; Avni, T; Battat, R; Eliakim, R; Koulaouzidis, A
Abstract : Introduction: Faecal calprotectin (FC) is a well-established marker of gut inflammation. While the correlation of elevated FC levels with colonic inflammation has been confirmed in several studies, 1, 2 data regarding the correlation of FC with small-bowel inflammation is either scarce or conflicting. 3 Capsule endoscopy (CE) is the modality of choice for detection of small-bowel inflammation and/or small-bowel Crohn's disease (CD). 4 Therefore, we aimed to systematically review and meta-analyse the evidence for the diagnostic accuracy of FC as a predictor of small-bowel CD. Methods: A comprehensive literature search of the databases PubMed and Embase was performed, using the search string: "capsule endoscopy" + calprotectin. Studies including patients with suspected and/or established CD evaluated by both FC and CE were retrieved. Corresponding authors were contacted for any missing data. The following FC cut-offs were evaluated: >50, 100 and 200 μg/g, as available in each included study. A diagnostic meta-analysis was performed; pooled diagnostic sensitivity (Se), specificity (Sp) and diagnostic odds ratio (DOR) with 95% confidence intervals (95% CI) were obtained for each of the cut-offs. Bias was evaluated using the quality assessment of studies of diagnostic accuracy in systematic reviews (QUADAS) 2 tool. A minimum of 4 studies was required for each analysis. Results: A total of 135 studies were identified; seven (3 prospective, 4 retrospective) studies, including 463 patients, entered the final analysis. Overall, the methodological quality of the studies was high, with 6/7 studies showing low risk of bias. For studies including only patients with suspected CD, the diagnostic accuracy of FC for the cut-off of 50 μg/g was as follows: 5 studies, 305 patients; Se 89% (CI 68%;97%), Sp 55% (CI 36%;73%), DOR 10.3 (CI 3.7;28.6) . For all included studies (suspected and established CD), the DOR was significant for all the evaluated FC cut-offs. FC > 50μg/g : 7 studies, 463 patients; Se 83% (CI 73%;90%), Sp 53% (CI 36%;71%), DOR 5.64 (CI 3.2;10.1). FC > 100μg/g : 5 studies, 379 patients; Se 68% (CI 56%;76%), Sp 71% (CI 46%;88%), DOR 5.01 (CI 2.03;12.07). FC > 200μg/g : 4 studies, 309 patients; Se 42% (CI 26%;64%), Sp 94% (CI 64%;99%), DOR 13.64 (CI 2.01;88.6). Sensitivity analysis based on methodological quality did not change those results significantly. Conclusion: This meta-analysis confirms that FC, when used as a predictor of small-bowel CD prior to CE, has high diagnostic accuracy. For patients with suspected CD, a FC cut-off level of 50 μg/g provided high sensitivity and DOR, while for the entire patient cohort (suspected and established CD) FC > 200 μg/g provided the best overall DOR. The likelihood of diagnosing small-bowel CD is extremely low in suspected CD patients with FC < 50μg/g. References: 1 D'Haens G, et al . Faecal calprotectin is a surrogate marker for endoscopic lesions in inflammatory bowel disease. Inflamm Bowel Dis 2012;18 :2218–2224. 2 Van Rheenen PF, et al . Faecal calprotectin for screening of patients with suspected inflammatory bowel disease: diagnostic meta-analysis. BMJ 2010;341 :c3369. 3 Mao R, et al . Faecal calprotectin in predicting relapse of inflammatory bowel diseases: A meta‐analysis of prospective studies. Inflamm Bowel Dis 2012;18 :1894–1899. 4 Annese V, et al . European evidence based consensus for endoscopy in inflammatory bowel disease. J Crohns Colitis 2013;7 :982–1018. Disclosure of Interest: None Declared